Perancangan Sistem Transaksi Penjualan Produk Berbasis Website Menggunakan Metode Agile (STUDI KASUS : RUMAH MAKAN SAUNG SULTAN) - Fadly Adrian; Grace Juliano Valmida; Muhamad Trio Fauzi (Shofanah Media Berkah, 2023)
A product sales transaction system is a system used to facilitate the buying and selling process between a seller and a buyer. In a business context, this system is typically used by stores, supermarkets, or other companies that sell products to customers. The main function of a product sales transaction system is to record the sales transactions that occur between the seller and the buyer. With this system, every sales transaction can be accurately and organizedly recorded, ensuring that important information about the products sold, prices, quantities, and customer details can be properly stored. In the business context, the product sales transaction system becomes a key element that supports operational success. This system not only functions to record sales transactions but also to manage inventory, generate financial reports, and manage customer data. One of the main components of a product sales transaction system is the hardware and software used. Commonly used hardware includes cash registers, barcode scanners, receipt printers, and electronic payment terminals. Meanwhile, the software is typically in the form of specialized applications that enable product sales, inventory management, and transaction tracking